2013
DOI: 10.1021/jp405065d
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Sum Frequency Generation Spectroscopy of Secondary Organic Material Produced by Condensational Growth from α-Pinene Ozonolysis

Abstract: Secondary organic material (SOM) was produced in a flow tube from α-pinene ozonolysis, and collected particles were analyzed spectroscopically via a nonlinear coherent vibrational spectroscopic technique, namely sum frequency generation (SFG). The SOM precursor α-pinene was injected into the flow tube reactor at concentrations ranging from 0.125 ± 0.01 ppm to 100 ± 3 ppm. The oxidant ozone was varied from 0.15 ± 0.02 to 194 ± 2 ppm. The residence time was 38 ± 1 s. The integrated particle number concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 66 publications
1
49
0
Order By: Relevance
“…In addition, further comparison studies using the technique introduced by Zhang et al (2015) and the poke-and-flow technique used here would be beneficial. Finally, the studies here are carried out at production mass concentrations greater than those found under ambient conditions (Hallquist et al, 2009;Slowik et al, 2010). Studies carried out using material produced under ambient conditions would provide further useful information.…”
Section: Effect Of Production Mass Concentration Used When Generatingmentioning
confidence: 99%
“…In addition, further comparison studies using the technique introduced by Zhang et al (2015) and the poke-and-flow technique used here would be beneficial. Finally, the studies here are carried out at production mass concentrations greater than those found under ambient conditions (Hallquist et al, 2009;Slowik et al, 2010). Studies carried out using material produced under ambient conditions would provide further useful information.…”
Section: Effect Of Production Mass Concentration Used When Generatingmentioning
confidence: 99%
“…The following two sections discuss the results obtained from the epoxides and the tetraols, and the last section compares the results to those obtained from the synthetic and field-derived SOA particle samples. We recently described the origin of the SFG response for well-characterized α-pinene-derived SOA particle material (Shrestha et al, 2013). In that work, we point out that the ssp-polarized SFG signals produced by the C-H oscillators originate from a non-centrosymmetric environment, i.e., a surface or interface.…”
Section: Vibrational Sum Frequency Generation Spectramentioning
confidence: 99%
“…Another further challenge for studying and understanding SOM is that it has a dynamic hygroscopic response to relative humidity, meaning that water is taken up and released with cycles in RH (Varutbangkul et al, 2006). The properties of organic particles, including viscosity, change with the fractional water content in the material (Zobrist et al, 2011;Renbaum-Wolff et al, 2013;Shrestha et al, 2014;Wang et al, 2014). Even so, advances on these challenges are needed because SOM in the atmosphere occurs in the aerosol form, and the surrounding environment in the planetary boundary layer regularly undergoes cycling between low and high RH, implying a dynamic state in the viscosity of SOM that is not well understood or quantified at present.…”
Section: Introductionmentioning
confidence: 99%